MODAL SOSIAL KELOMPOK WANITA NELAYAN DI KELURAHAN LAPULU KECAMATAN ABELI KOTA KENDARI - Wa Ode Miftahul Jannah; Hartina Batoa; Salahuddin Salahuddin; Sitti Nur Isnian (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The objective of this study is to ascertain the implementation of social capital elements among women fishermen in Lapulu Village. The research population consists of all women fishermen who are members of women fishermen groups in Lapulu Village, with a total sample size of 30 individuals. The sample was determined using a census method. The data were collected through a variety of methods, including in-depth interviews, documentation analysis, a review of existing literature, and the administration of surveys. The variables in this study were social capital, defined as a multifaceted concept encompassing trust, social norms, and networks. The collected data were then subjected to a quantitative statistical analysis, employing descriptive statistical analysis methods. The results of the study indicate that the application of social capital among women fishermen in Lapulu Village is in the good category, with a dominance in the dimension of trust (83%), followed by social norms (70%), and social networks (43%). The elevated level of trust fosters cooperation, information disclosure, and solidarity among members. The concept of social norms is exemplified by the adherence to group rules and cultural practices, such as the act of praying prior to engaging in business activities. Concurrently, constrained access to technology and inadequate educational attainment contribute to suboptimal utilization of social networks. The elements of social capital are effectively implemented by combining the local wisdom of the fishing community with digital literacy, which can serve as a key to enhancing the sustainable empowerment of female fishermen.